DNA methylation and psychotherapy response in trauma-exposed men with appetitive aggression. (January 2021) - Xulu, Khethelo R.; Womersley, Jacqueline S.; Sommer, Jessica; Hinsberger, Martina; Elbert, Thomas; Weierstall, Roland; Kaminer, Debbie; Malan-Müller, Stefanie; Seedat, Soraya; Hemmings, Sian M.J.
Highlights: FORNET treatment reduces appetitive aggression and PTSD symptom scores AUTS2 and NR4A2 methylation are inversely associated with PTSD symptom severity TFAM methylation is positively associated with appetitive aggression scale scores Dopaminergic signalling and synaptic plasticity influence PTSD symptom severity Oxidative phosphorylation capacity is implicated in appetitive aggression Abstract: Exposure to violence can lead to appetitive aggression (AA), the positive feeling and fascination associated with violence, and posttraumatic stress disorder (PTSD), characterised by hyperarousal, reexperience and feelings of ongoing threat. Psychotherapeutic interventions may act via DNA methylation, an environmentally sensitive epigenetic mechanism that can influence gene expression. We investigated epigenetic signatures of psychotherapy for PTSD and AA symptoms in South African men with chronic trauma exposure. Participants were assigned to one of three groups: narrative exposure therapy for forensic offender rehabilitation (FORNET), cognitive behavioural therapy or waiting list control ( n  = 9-10/group). Participants provided saliva and completed the Appetitive Aggression Scale and PTSD Symptom Severity Index at baseline, 8-month and 16-month follow-up. The relationship, over time, between methylation in 22 gene promoter region sites, symptom scores, and treatment was assessed using linear mixed models. Compared to baseline, PTSD and AA symptom severity were significantly reduced at 8 and 16 months, respectively, in the FORNET group. Increased methylation of genes implicated in dopaminergic neurotransmission ( NR4A2 ) and synaptic plasticity ( AUTS2 ) was associated with reduced PTSD symptom severity in participants receiving FORNET. Analyses across participants revealed a proportional relationship between AA and methylation of TFAM, a gene involved in mitochondrial biosynthesis.